SOSIALISASI REGULASI IZIN PEREDARAN DAN LABEL HALAL PRODUK PANGAN DALAM MENINGKATKAN NILAI PENJUALAN UMKM DI LINGKUNGAN RW 05 PINANG GRIYA-PINANG TANGERANG - Desy Anggraeni; Nazori AZ; Wulandari Wulandari (Jurnal Padamu Negeri, 2025)
In this community service activity, the initiative was carried out with a group of residents who run home-based businesses and are part of the MSME (Micro, Small, and Medium Enterprises) group in RW 05 Pinang Griya. Several of these entrepreneurs—most of whom produce food and beverages—are still unfamiliar with the regulations regarding food distribution permits and halal certification for their products. This knowledge is essential to ensure that their products are recognized and guaranteed to be halal. Starting in 2026, Article 160 paragraph (2) stipulates that micro and small business actors (UMK) are subject to a phased obligation for halal certification for food products, beverages, slaughtered goods, and slaughter services. This regulation is expected to influence consumer awareness, particularly regarding the products they purchase. As Indonesia is a Muslim-majority country, such regulation will encourage UMK businesses to certify their products as halal. This, in turn, is expected to positively impact sales performance and contribute to improving the local economic conditions.